Existence of Nontrivial Steady State of a Chemotaxis Fluid Coupled System (Journal of Partial Differential Equations, 2025)
This paper studied a chemotaxis fluid coupled system which models theso-called “chemotactic Boycott effect”. Under certain inhomogeneous boundary conditions, we proved the existence of nontrivial steady state which depends only on onevariable of such system in $[0,1]^3.$ A positive lower bound of the oxygen concentration $c$ was also obtained.
Keywords: Chemotaxis; Navier-Stokes equations; steady state; mixed boundary conditions.